Opposed Yet Embraced: Authenticity, Aesthetics, and Reception of I‘tirâf Poem among Traditional Muslims in Indonesia - Ahmad, Lalu Turjiman; Ismatullah, Dadang; Zakaria, Zarima Mohd (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2025)
The I‘tiraf poem, often attributed to Abū Nuwās, is a significant work of Arabic literature widely known in Indonesia, especially among traditional Muslims. Although its authorship has long been debated, the poem remains alive through religious practices. This study employs a philological approach to examine its authenticity and applies literary reception theory to explore its dynamic interpretations and aesthetic dimensions using the Arabic rhetorical and stylistics approach (Balagah and Uslūbiyyah). The findings indicate that the attribution of the poem to Abū Nuwās is not genuine. However, the poem has been creatively received and localized: recited after Friday prayers in Banten during the handshake (mushafahah), incorporated into the Ḥizb Nahdlatul Wathan in Lombok, and chanted during zikr (invocation) and ḥaul (commemoration) rituals in Palembang. Its rhetorical strength and emotional depth make it a powerful spiritual medium, transforming it from a classical Arabic text into a collective prayer shaping Indonesian Muslim identity.